Collapsing Glomerulopathy Superimposed on Diabetic Nephropathy - Etta, Praveen Kumar (Indian J Nephrol, 2019)
Diabetic nephropathy (DN) is characterized by gradually progressive renal failure and proteinuria. Various types of nondiabetic kidney diseases may superimpose on DN, and affect the natural course, prognosis, and management. Collapsing glomerulopathy (CG) is a form of glomerular proliferative injury, characterized by rapid progression and associated with poor prognosis. CG may be idiopathic or secondary to other causes, and it has also been described with other forms of glomerular diseases. The association of CG with DN has not been reported widely. We report on a patient with DN who has undergone renal biopsy due to massive proteinuria and rapid loss of renal function. Renal biopsy was suggestive of CG superimposed on DN. He was treated conservatively, however, progressed to end-stage renal disease rapidly.